Analisis Penyebab Kecacatan Produk Plastic Injection dengan Metode Failure Mode and Effect Analysis di PT OPQ - Ihsan, Muhammad; Fasa, Nadia (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
The manufacturing industry is required to maintain product quality to meet standards and reduce the level of defects in the production process. PT OPQ, which is engaged in the production of injection plastics, faces the problem of product defects that can affect operational efficiency and customer satisfaction. Therefore, an in-depth analysis is required to identify the cause of the defect and determine the appropriate improvement strategy. This study uses the Failure Mode and Effect Analysis (FMEA) method to identify the type of product defect, analyze the causative factors, and determine the priority of handling based on the calculation of the Risk Priority Number (RPN). Data was collected through direct observation, interviews with the production team, and analysis of production documents during the period from March to April 2024. The results showed that the main defects that occurred included incomplete mold (RPN 294), cracks (RPN 168), curved products (RPN 150), and excessive materials (RPN 100). The main causative factors are lack of material, uneven cooling, and errors in the injection and mold removal process. The application of the FMEA method allows companies to identify critical points in the production process and set more effective improvement priorities. With the improvement based on the results of this analysis, PT OPQ can improve product quality, reduce defect rates, and increase efficiency and customer satisfaction. Keywords: FMEA, product defects, production efficiency. quality control, RPN